Strategic Infectious Diseases in Beef Cattle in Balongpanggang during 2023 - Wiwik Misaco Yuniarti; Bambang Sektiari Lukiswanto; Boedi Setiawan; Ira Sari Yudaniayanti; Nusdianto Triakoso; Mirza Atikah Madarina Hisyam; Lina Susanti; Apriliwiyani Niken Hastuti; Budi Santoso Sudjono (Jurnal Medik Veteriner)
Strategic infectious animal diseases have a great impact on the national economy as they may cause great economic loss, public anxiety, and high mortality. In Indonesia, among the diseases considered as strategic infectious animal diseases is foot and mouth disease (FMD). This study reported the incidence of strategic infectious animal diseases in Balongpanggang district during 2023. Throughout 2023, FMD only accounted for 4% of the total diseases of the year and was the only strategic infectious animal disease reported that year. Meanwhile, bovine ephemeral fever (BEF) incidence reached 57% (876/1546) of the total diseases in beef cattle in 2023. In addition to BEF, official veterinary services reported a total case of 1546 throughout 2023 that comprises; diarrhea (99), limping (24), helminthiasis (91), ectoparasite (11), hematochezia (3), wound (3), mastitis (4), allergy (1), dystocia (28), vaginal prolapse (11), dermatitis (45), enteritis (27), tympani (11), scabiosis (122), arthritis (67), ophthalmic problem (11), endometritis (1), uterine retention (13), indigestion (2), pneumonia (21), hypoglycemia (5), abscess (21), ovariohysterectomy (1), orchitis (1), intoxication (1), and papilloma (1). In conclusion, the only strategic infectious animal disease reported in 2023 in Balongpanggang was FMD with the incidence as high as 3% as compared to the non-strategic infectious animal diseases, BEF, which reached 54% of the total cases during 2023.